New Players in the Same Old Game: Disturbance of Group 2 Innate Lymphoid Cells in HIV-1 and Mycobacterium leprae Co-infected Patients. - Pedro Henrique Papotto; Solange Maeda; Jane Tomimori; Marília Brasil Xavier; Luiz Vicente Rizzo; Esper Georges Kallas; Karina Inácio Carvalho (Public Library of Science (PLoS), 2015)
Leprosy control is achieved through a fine-tuning of TH1 and TH2 immune response pattern balance. Given the increasing epidemiological overlay of HIV and M. leprae infections, immune response in co-infected patients consists in an important contemporary issue. Here we describe for the first time the innate lymphoid cells compartment in peripheral blood of leprosy and HIV/M. leprae co-infected patients, and show that co-infection increases group 2 innate lymphoid whilst decreasing group 1 innate lymphoid cells frequencies and function.